Transcriptomic analysis of staphylococcal sRNAs: insights into species-specific adaption and the evolution of pathogenesis. Issue 7 (26th April 2016) - Broach, William H.; Weiss, Andy; Shaw, Lindsey N.
Abstract : Next-generation sequencing technologies have dramatically increased the rate at which new genomes are sequenced. Accordingly, automated annotation programs have become adept at identifying and annotating protein coding regions, as well as common and conserved RNAs. Additionally, RNAseq techniques have advanced our ability to identify and annotate regulatory RNAs (sRNAs), which remain significantly understudied. Recently, our group catalogued and annotated all previously known and newly identified sRNAs in several Staphylococcus aureus strains. These complete annotation files now serve as tools to compare the sRNA content of S. aureus with other bacterial strains to investigate the conservation of their sRNomes. Accordingly, in this study we performed RNAseq on two staphylococcal species, Staphylococcus epidermidis and Staphylococcus carnosus, identifying 118 and 89 sRNAs in these organisms, respectively. The sRNA contents of all three species were then compared to elucidate their common and species-specific sRNA content, identifying a core set of between 53 and 36 sRNAs encoded in each organism. In addition, we determined that S. aureus has the largest set of unique sRNAs (137) while S. epidermidis has the fewest (25). Finally, we identify a highly conserved sequence and structural motif differentially represented within, yet common to, both S. aureus and S. epidermidis. Collectively, in this study, we uncover the sRNome common to three staphylococcal species, shedding light on sRNAs that are likely to be involved in basic physiological processes common to the genus. More significantly, we have identified species-specific sRNAs that are likely to influence the individual lifestyle and behaviour of these diverse staphylococcal strains.